Strategi DPMPTSP dalam Pemberdayaan UMKM melalui Pendampingan Pengurusan SPP-IRT di Kota Surabaya - Agung, Agung; Ramadhan, Andhika Akbar; Syaputra, Fajar Tridian; Wahyudi, Kalvin Edo (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the role of the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) in empowering Micro, Small, and Medium Enterprises (MSMEs) through assistance in obtaining Home Industry Food Production Certificates (SPP-PIRT). MSMEs, as a crucial pillar of the local economy, require business legality to expand market access and enhance competitiveness, especially in facing global economic challenges. One form of legality required is SPP-PIRT, which ensures the quality and safety of food products. The research employs a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation. The findings reveal that DPMPTSP Surabaya has implemented various strategies to raise MSME awareness about the importance of business legality through socialization, training, and technical assistance. The results indicate a significant increase in the number of SPP-PIRT certificates issued, particularly in 2022 and 2023. However, a sharp decline in 2024 highlights challenges in sustaining the assistance program. Through SWOT analysis, the study identifies DPMPTSP's strengths, such as government support and technological infrastructure, while also uncovering weaknesses related to MSMEs' dependency on assistance. It is recommended that DPMPTSP enhance sustainable training programs, strengthen collaboration with stakeholders, and adopt more adaptive and continuous assistance approaches to boost MSME competitiveness in Surabaya.